Hifz Al-Bi'ah as Part of Maqashid Al-Shari'ah and Its Relevance in the Context of Global Climate Change - Khuluq, M. Khusnul; Asmuni, Asmuni (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2024)
The five essential principles (dharuriyyat al-khamsah) proposed by As-Syatibi, encompassing the preservation of religion, self, progeny, wealth, and intellect, were highly progressive concepts in their time. However, today we face the challenge of global climate change threatening ecosystems and humanity. Thus, the concept of hifz al-bi’ah becomes crucial as a new variable within the scope of essential principles. This research employs a qualitative approach with a literature review study. The data utilized include literature covering classical and contemporary sources, scientific research, and policy documents related to global climate change. The results of this study indicate that the concept of hifz al-bi’ah was initially developed through environmental jurisprudence (fiqh al-bi’ah) and evolved into hifz al-biah, an integral part of maqasid al-shariah. Hifz al-bi’ah serves as a foundation for the implementation of hifz al-din, hifz al-nafs, hifz al-nasl, hifz al-mal, and hifz al-'aql. Simultaneously, the aspects of essential principles are expanded, systematically placing hifz al-bi’ah in a crucial position within them. In the context of global climate change threatening ecosystems and the existence of humanity, the concept of hifz al-bi’ah as part of maqashid al-shariah is highly relevant in efforts to mitigate or even reverse global climate change.